Everyday Revolutionaries : Gender, Violence and Disillusionment in Postwar El Salvador. - Silber, Irina Carlota (Genocide, political violence, human rights series., 2010)
Everyday Revolutionaries provides a longitudinal and rigorous analysis of the legacies of war in a community racked by political violence. By exploring political processes in one of El Salvador's former war zones-a region known for its peasant revolutionary participation-it offers a searing portrait of the entangled aftermaths of confrontation and displacement, aftermaths that have produced continued deception and marginalization. Beautifully written and offering rich stories of hope and despair, this book contributes to important debates in public anthropology and the ethics of engage.